Food Handling Practices among Food Handlers of Eating Establishments in the Government Hospitals, Mandalay City, Myanmar - , Si Thu Aung; , Aung Aung Nwe; , War War Shan; , Soe Moe Naing; , San San Htay; , Kyaw Kyaw (Archives of Current Research International, 2019)
Background: Hospital environment is a favourable condition for growing of pathogens. Unhygienic practices of food handlers and contaminated food may be the cause of foodborne diseases, resulting in much comorbidity and longer hospital stay of the affected persons. Aims: To study socio-demographic characteristics, working characteristics and food handling practices among food handlers of eating establishments in the government hospitals, Mandalay city, Myanmar. Study Design: Cross-sectional descriptive study. Place and Duration of Study: One hundred and eleven eligible food handlers from government hospitals in Mandalay city, Myanmar between May 2018 and August 2018. Methodology: Face to face interviews with all eligible food handlers were carried out with pretested questionnaire. Observational checklist was used for current situation of food handlers. Results: The majority of employees were female and full-time food handlers. No pre-employment and periodic medical examinations of food handlers were done. More than half (54.05%) of total food handlers had unsatisfactory on food handling practices. Food handling practices status was influenced by duration of working in the current jobs (P=.001). Conclusion: There was high status of unhygienic food handling practices of the food handlers working in the eating establishments of the government hospitals, Mandalay city, Myanmar.